2022
DOI: 10.1186/s12889-022-13777-7
|View full text |Cite
|
Sign up to set email alerts
|

Mental health indicators and their lifestyle associations in German students: a gender-specific multivariable analysis

Abstract: Background Statistics show that the number of received psychosocial counselling sessions remains at a constantly high level or has even increased since the COVID-19 pandemic situation in 2020. The objective of this work is to identify factors associated with students’ mental health to improve prevention and promotion in mental health at universities. Methods The analyses were based on a cross-sectional data set collected by an online survey among 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…In terms of anxiety, 34% of the current sample screened positive, less than in the USA where 61% of college students reported feeling overwhelming anxiety [13]. We observed that female sex was associated with a higher prevalence of screening positive for anxiety, supporting previous research among college/university students from China, the USA, and Germany [78][79][80]. However, among undergraduates in India, there was a significant association of male sex with anxiety only among second year medical students [81], and others reported no significant gender differences in anxiety [82,83].…”
Section: Student Mental Health By Sexsupporting
confidence: 84%
“…In terms of anxiety, 34% of the current sample screened positive, less than in the USA where 61% of college students reported feeling overwhelming anxiety [13]. We observed that female sex was associated with a higher prevalence of screening positive for anxiety, supporting previous research among college/university students from China, the USA, and Germany [78][79][80]. However, among undergraduates in India, there was a significant association of male sex with anxiety only among second year medical students [81], and others reported no significant gender differences in anxiety [82,83].…”
Section: Student Mental Health By Sexsupporting
confidence: 84%
“…These factors impair academic performance ( 65 ). Studies indicate that women have reported worse mental health than men ( 66 ), highlighting gender differences in mental health, which is a matter of great concern, as it does not contribute to the overall well-being of women and hinders their emotional and social progress and development ( 67 ).…”
Section: Post-covid-19 Pandemic: Diagnosis Of Mental Health In Chilea...mentioning
confidence: 99%